Consistency of Helicobacter pylori eradication rates of first‐line concomitant and sequential therapies in Korea: A nationwide multicenter retrospective study for the last 10 years. Issue 2 (17th February 2021) - Lee, Bong Eun; Kim, Joon Sung; Kim, Byung‐Wook; Kim, Jie‐Hyun; Kim, Jin Il; Chung, Jun‐Won; Jeon, Seong Woo; Lee, Jeong Hoon; Kim, Ji Hyun; Kim, Nayoung; Lee, Ju Yup; Seo, Seung Young; et al.
Abstract: Background: Eradication rate of standard triple therapy for H .  pylori has declined to unacceptable level, and alternative regimens such as concomitant and sequential therapy have been introduced. We aimed to assess the consistency of eradication rates of concomitant and sequential therapies as for the first‐line H .  pylori eradication in Korea. Methods: A nationwide multicenter retrospective study was conducted including 18 medical centers from January 2008 to December 2017. We included 3, 800 adults who had test to confirm H .  pylori eradication within 1 year after concomitant or sequential therapy. Results: Concomitant and sequential therapy were prescribed for 2508 and 1292 patients, respectively. The overall eradication rate of concomitant therapy was significantly higher than that of sequential therapy (91.8% vs. 86.1%, p  < .001). In time trend analysis, the eradication rates of concomitant therapy were 90.2%, 88.2%, 92.1%, 94.3%, 91.1%, and 93.4% for each year from 2012 to 2017 with an increasing trend ( p  = .0146), while those of ST showed no significant trend ( p  = .0873). Among 263 patients with second‐line therapy, bismuth quadruple therapy showed significantly higher eradication rate than quinolone‐based triple therapy (73.9% vs. 51.5% in ITT analysis, p  = .001; 82.7% vs. 63.0% in PP analysis, p  = .002). Conclusion: Concomitant therapy is the best regimen for the first‐line H. pylori eradication showing consistently higher eradication rate with an increasing trend for the last 10 years in Korea. Bismuth quadruple therapy should be considered for second‐line therapy after eradication failure using non‐bismuth quadruple therapy.